The Development of Electronic Student Worksheets (E-LKPD) Integrated with Islamic Values on Human Respiratory System Material at Grade VIII - Tamara, Nabila Luthfidia; Hakim, Nasrul (IAIN Kendari, 2024)
The present study aims to develop, validate, and analyze teacher's and students' responses to a product of electronic-student worksheets (i.e. elektronik-Lembar Kerja Peserta Didik or e-LKPD) which are integrated with Islamic values on a biology subject at grade VIII regarding the topic of human respiratory system. This research was carried out in two different places, namely at the Biology Study Program of IAIN Metro where the e-LKPD product was designed by the researchers and was validated by material experts and media experts at the university, and at SMP Negeri 1 Way Jepara to test the e-LKPD product (on a teacher and a small group of students). The present study is a development study using the ADDIE model, which consists of analysis, design, development, implementation. and evaluation stages. The results show: 1) the e-LKPD integrated with Islamic values at the learning topic of human respiratory system involves an understanding of the organs, mechanisms and disorders that occur in the human respiratory system which is connected and viewed from Islamic principles (application of Islamic moral and ethical values within the act of breathing); 2) The results of the validity test for the material aspect of the e-LKPD were 86% which is categorized as very good meaning the material can be placed on the e-LKPD template that was to developed; 3) The results of the validity test for the aspect of the e-LKPD media were 90% which is categorized as very good allowing the e-LKPD media arrangement to be firmly established; 4) The teacher's response to the e-LKPD being developed was 93% which is categorized as very feasible, and the students' response to the e-LKPD being developed was 94% which is categorized as very practical, implying that the e-LKPD materials and its media are already suited to the needs of the learning process, so it can be concluded that the developed e-LKPD integrated with Islamic values can be used in the biology learning activities at grade VIII about the human respiratory system.